Thymoquinone in Ocular Neurodegeneration: Modulation of Pathological Mechanisms via Multiple Pathways - Mahmud, Nur Musfirah; Paraoan, Luminita; Khaliddin, Nurliza; Kamalden, Tengku Ain (Frontiers in Cellular Neuroscience, 2022)
Thymoquinone is a naturally occurring compound and is the major component of Nigella sativa, also known as black seed or black cumin. For centuries thymoquinone has been used especially in the Middle East traditionally to treat wounds, asthma, allergies, fever, headache, cough, hypertension and diabetes. Studies have suggested beneficial effects of thymoquinone to be attributed to its antioxidant, antibacterial, anti-oxidative stress, anti-inflammatory and neuroprotective properties. Recently, there has been a surge of interest in thymoquinone as a treatment for neurodegeneration in the brain, such as that seen in Alzheimer's (AD) and Parkinson's diseases (PD). In vitro and in vivo studies on animal models of AD and PD suggest the main neuroprotective mechanisms are based on the anti-inflammatory and anti-oxidative properties of thymoquinone. Neurodegenerative conditions of the eye, such as Age-related Macular Degeneration (AMD) and glaucoma share at least in part similar mechanisms of neuronal cell death with those occurring in AD and PD. This review aims to summarise and critically analyse the evidence to date of the effects and potential neuroprotective actions of thymoquinone in the eye and ocular neurodegenerations.